A characterization of the weighted version of McEliece-Rodemich-Rumsey-Schrijver number based on convex quadratic programming - Luz, Carlos J. (2018)
For any graph $G,$ Luz and Schrijver \cite{LuzSchrijver} introduced a characterization of the Lovász number $ϑ(G)$ based on convex quadratic programming. A similar characterization is now established for the weighted version of the number $ϑ^{′}(G),$ independently introduced by McEliece, Rodemich, and Rumsey \cite{McElieceetal} and Schrijver \cite{Schrijver1}. Also, a class of graphs for which the weighted version of $ϑ^{′}(G)$ coincides with the weighted stability number is characterized.